Intervention, Interest Rates, and Charts : Three Essays in International Finance - Taylor, Mark (IMF Working Papers; Working Paper ;, 1991)
This paper contains essays on sterilized intervention, on covered interest rate parity, and on chartist analysis in financial markets. Each essay contains a definition, brief survey of the empirical evidence and overall assessment of each topic.